Legal Protection of Personal Data in Online Loans - Citra Khairina Maharani Safari (Outline Publisher, 2025)
Inheritance disputes often arise when the execution of a will exceeds the free portion and harms the rights of the heirs protected by the principle of legitime portie in the Civil Code. This study aims to analyze the legal consequences of the execution of a will that is detrimental to the heirs and to assess the status of a will deed that is unknown to the heirs or the recipients of the will. The method used is normative juridical research with a statutory and conceptual approach, supplemented by a review of relevant jurisprudence. The analysis is carried out qualitatively and doctrinally on the norms governing wills, the protection of legitime portie, and legal remedy mechanisms. The results of the study indicate: (1) the execution of a will that exceeds the free portion is not immediately null and void by law, but can be requested for reduction (inkorting) by the heirs until their legitime portie is fulfilled; (2) an authentically made will deed remains formally valid as long as it meets the requirements of form, but its validity is relative and can be limited by a court decision to the extent that it violates legitime portie; (3) the heirs' ignorance of the existence of a will does not invalidate its validity, but has implications for the enforcement of rights—including through requests to open the will, requests for copies, and lawsuits for reductions against the will recipients/executors; (4) the final legal consequences are in the form of a recalculation of the distribution of the inheritance and the obligation to return by the will recipients for the portion that exceeds the provisions. This finding emphasizes the importance of transparency and compliance with the limits of legitime portie to prevent disputes and provide legal certainty for the parties.